Arhitecturi urbane în proza lui Mihai Eminescu - Roxana Patraș (Revista de Istorie și Teorie Literară)
The present paper represents a development of my article Proza eminesciană în câteva clişee critice: rusticitate şi urbanitate. By relating Mihai Eminescu’s fundamental urbanity with the Realist trend in the European novel, on the one hand, and with the reading expectance of the Romanian public, on the other, I endeavour to establish a few coordinates of urban experience into fiction. The first part of my analysis focuses on Eminescu’s reaction (emulation, difference) to the narrative patterns and to typologies of the French Realist novel. As proven by early short-stories and sketches, the male characters inherit the impulse of upward mobility, which is specific for Realist prose. However, once the map of the characters’ journeys (Cluj–Bucureşti–Iaşi–Copenhaga–Torino–Hohenschwangau– Sankt-Persburg–Sevilla) grows more and more Gothic, the relationship individual-environment loses its tensed appearance. Thus, my research tracks down two types of architectural perception that change the inner structure of Eminescu’s characters and turn them into “Gothic spirits”: the first is formed by instances of visual apprehension of Gothic traits, especially redundancy; the second refers to those moments of vision, when the architecture of the universe is revealed, and “miniature” is turned into “cathedral”, and the invisible is made visible. Eminescu has the intuition of their coincidence and, by that, his prose moves from a Realist model to the more elaborated style of uncanny stories.